EFFECTS OF PHYSICAL EXERCISES ON TRIACYLGLYCEROL LEVEL IN SKELETAL MUSCLES IN DIETARY-INDUCED OBESE RATS - I. Yu. Yakimovich; D. A. Borodin; I. K. Podrezov; V. V. Ivanov; V. N. Vasiliyev; M. Yu. Kotlovsky (Бюллетень сибирской медицины)
The accumulation of triacylglycerol in peripheral tissues is one of mechanisms of insulin resistance. This paper presents the investigation of the influence of aerobic and anaerobic physical exercises on triacylglycerol level in skeletal muscles and on insulin resistance in dietary-induced obese rats. It is estimated that a high-energy (HE) diet causes the accumulation of triacylglycerols in skeletal muscles that leads to high resistance to insulin. Aerobic and anaerobic physical exercises reduce the level of triacylglycerols in skeletal  muscles  and  raise  sensitivity to  insulin  in  obese  rats.  Physical  exercises  raise  the  level  of triacylglycerols in skeletal muscles in standard-diet rats that probably is the adaptation to high energy expenditure, but does not lead to high insulin resistance.